The role and value of the principle of the rule of law in administrative and business relations - Shulga, Ievgenii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
In this article, the role and significance of the rule of law in administrative and delict relations, as well as its place among other principles of law, are explored. On the basis of the analysis of the domestic principles of the rule of law principle, its components have been investigated, and through the study of international legal norms, new components of it have been identified and proposed for implementation. The attention was paid to the necessity of expanded legislative consolidation of the principle of the rule of law and its constituent elements in the proper manner in the course of the drafting of the administrative-delict code of Ukraine. A number of cases brought to the European Court of Human Rights have been analyzed. It was concluded that the principle of the rule of law in its essence includes all other principles that could be attributed to the principles of administrative and tort relations. In view of the necessity and the utmost importance of observance of the rule of law principle, in our opinion, it should be fixed in the codified normative legal acts (in the Administrative Tort Code). And in order to avoid any misunderstandings and its free interpretation, all its components should be recorded